Screening for latent tuberculosis infection in patients with inflammatory bowel disease: Can interferon-gamma release assays replace the tuberculin skin test? - Cabriada, José Luis; Ruiz-Zorrilla, Rafael; Barrio, Jesús; Atienza, Ramón; Huerta, Alain; Rodríguez-Lago, Iago; Antonio, Antonio; Herrero, César (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Screening for latent tuberculosis infection is mandatory before starting anti-tumor necrosis factor therapy. New assays based on interferon-γ (IFN-γ) release have recently become available and may be more accurate. The aim of this study was to compare QuantiFERON-TB and tuberculin skin test in screening for latent infection in patients with inflammatory bowel disease. Materials and Methods: We prospectively screened 138 patients with inflammatory bowel disease for latent tuberculosis infection with chest X-ray, tuberculin skin test, and a third-generation QuantiFERON-TB test. The association of the results in both tests with immunosuppression or inflammatory activity was determined by logistic regression. Results: The tuberculin skin test and QuantiFERON-TB were positive in 21.7% and 24.6% of the patients, respectively. Overall, 71% patients were receiving immunosuppressants. Concordance between the two tests was moderate (κ=0.59; 95% confidence interval (CI), 0.43-0.75) and was higher in immunosuppressant-naïve patients (κ=0.75; 95% CI, 0.52-0.97) than in immunosuppressed patients (κ=0.51; 95% CI, 0.30-0.72). In both the tests, disease activity and receiving immunosuppression were not associated with the test results. Nevertheless, QuantiFERON-TB was negatively influenced with two or more immunosuppressive drugs. Conclusion: Concordance between the two tests was moderate, and it appears lower with immunosuppression. QuantiFERON-TB alone may be appropriate in immunosuppressant-naïve patients. Both tests should be considered in immunosuppressed patients. Cite this article as: Cabriada JL, Ruiz-Zorilla R, Barrio J, et al. Screening for latent tuberculosis infection in patients with inflammatory bowel disease: Can interferon-gamma release assays replace the tuberculin skin test? Turk J Gastroenterol 2018; 29: 292-8.